The Polemic on Imposing Castration Sanctions against Pedophiles Perpetrators Based on the Human Right’s Perspective - Rakhmat Ubaidillah Ahror (Constitutionale, 2021)
Sexual violence is a crime against humanity. Because, it is, closely related to human rights Cases of sexual violence caused the government to issue the idea of castration for perpetrators of sexual violence. However, this raises pros and cons in the community. The problem of this research is, how is the imposition of castration sanctions on pedophiles from a human rights perspective, and what are the supporting and inhibiting factors for implementing castration sanctions against pedophiles? The study uses a normative juridical and empirical juridical approach carried out on theoretical matters of legal principles. In contrast, the empirical approach is carried out to study the law in reality through behavioural assessments. The study results stated that the perspective of imposing castration sanctions on pedophile perpetrators also reaped the pros and cons in its implementation. Some thought that castration sanctions were quite effective if applied to perpetrators of sexual crimes to immediately provide a deterrent effect on perpetrators and break the chain of sexual crimes that developed in the community. Opinions against the castration sanction are also criticised by various groups, including human rights activists, because castration is considered a cruel punishment for perpetrators, and cruel punishments aim to torture the perpetrators of the crime, but this is undoubtedly related to human rights. Supporting and inhibiting factors for the implementation of castration sanctions against pedophile perpetrators. Supporting factors for the discourse of castration sanctions on perpetrators of sexual crimes against children are caused by the high number of sexual crimes in Indonesia, which has entered a dangerous stage. It was passed into Law Number 17 of 2016. The inhibiting factor is that castration sanctions are not allowed in the national criminal law system. The purpose of punishment, castration is a violation of human rights, seen from the facilities or facilities. Furthermore, there are obstacles from the executor of the castration crime, namely doctors, because it contradicts the code of ethics (KODEKI). Suggestions in this study should be in imposing criminal acts of sexual violence against children to pay attention to humane punishments without degrading and provide benefits, namely a deterrent effect.